Building a model of the integrity of information resources within an enterprise management system - Ospanova, Gulmira; Kukharenko, Evgeniya; Ievlanov, Maksym; Panforova, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
In addressing the integrity of documents in modern information systems, the focus is on protecting them from unauthorized user changes. At the same time, the solution to the problem of ensuring the preservation of the composition, content, and interaction of documents has almost not been considered. However, such a task often has to be solved during the operation of information systems, as well as enterprise management systems handling unstable business processes. To address this issue, an approach has been proposed to unify solutions to the task related to the integrity of paper-based documents circulating within an enterprise management system, as well as electronic documents and stored information system data. The existing service registry models have been analyzed, aimed to formally describe the resources of the information system and an enterprise management system based on this information system. Models of elements of the unified information resource registry have been modified, and a model for ensuring the integrity of an enterprise’s information resources has been developed. The proposed improvements make it possible to use current and multi-tested methods to address the integrity of information resources. Experimental testing of improved models of a unified information resource registry has been carried out. The task of ensuring integrity was considered for a regulatory document that should change its name and its composition as a result of external and internal factors. It has been shown that the application of the proposed results makes it possible to solve the task of ensuring the integrity of information resources such as paper-based regulations of an enterprise management system, within the framework of a unified registry of information resources by existing database management systems